Al ritmo del funk: análisis interpretativo de la semicorchea en la batería de representantes relevantes del género a través de las décadas de 1970 y 1980 aplicado en arreglos de funk y R and B contemporáneo en un concierto final - Cabezas Guevara, Rommel Iván (2017)
The semiquaver (sixteenth note) belongs to the rhythmic notation system, and has taken a great part in the creation and development of various music genres such as funk, r and b, rock, and others. Throughout time it has become a very important element, and the key to define groove; because of the manner it sounds and the different ways it is expressed, articulated and performed by drum sets. It causes the instrumental interpretation of different genres to acquire a more nourished language. This investigation is focused on different drummers that are the most representative in the funk genre during the 70s and 80s, and that have overall, made an significant application of the sixteenth note in this style, such as: David Garibaldi, Dennis Chambers, Bernard Purdie, and John “Jabo” Starks. The analysis starts from specific aspects such as language, technique, style, and the function that each and every one of them give to the semiquaver, through musical transcriptions, and several analysis that have been made upon them with the purpose of showing that these performance techniques can be applied in contemporary music arrangements, especially in funk, and r and b, that have been mentioned earlier. The focus of this investigation is instrumental performance, which is why the final product of this project is a final concert where the use of the semiquaver, and the results obtained from this document will be applied and witnessed.